Sakeco sebagai Represntasi Local Genius: Kajian Konservasi Sastra Lisan Lawas Etnik Sumbawa: Sakeco as a Representation of Local Genius: A Study on the Conservation of Lawas Oral Literature in Sumbawa Ethnic Community - I Made Suyasa (Universitas Tidar, 2026)
Oral literature constitutes one of the cultural heritages that represents local wisdom and the identity of a community. Sakeco emerges as a form of traditional oral literature that functions not only as entertainment but also as a medium of communication, a means of moral education, and an artistic expression of Sumbawa society. This study aims to analyze the potential of Sakeco as a representation of local genius and to examine appropriate conservation strategies for maintaining its continuity amid the currents of modernization. The research method employed is descriptive qualitative with an ethnographic approach through literature review, observation, and interviews with cultural practitioners. The findings indicate that Sakeco embodies local wisdom values such as social solidarity, respect for nature, religiosity, social criticism, and community ethics that remain relevant to modern life. However, its existence currently faces challenges including declining interest among younger generations, lack of documentation, and minimal support from cultural policies. Therefore, conservation efforts for Sakeco need to be realized through the revitalization of performances in public spaces, integration of local wisdom-based education in schools, regeneration training for young artists, and utilization of digital media as a means of documentation and promotion. Thus, Sakeco can be preserved not merely as a cultural artifact but can also thrive as a dynamic identity of Sumbawa society that is rich in local genius.